Answer:
see below, I hope it's helpful
Explanation:
Simplifying expressions...
1. use as many steps as you need, don't take shortcuts or try to do too much in one step... only touch each item in the expression once at most at each step
2. Follow PEMDAS
3. consider some of the rules of exponents: (a/b)^n = (a^n)/(b^n) and (x)^(-n) = 1/(x^n) and a^(b^c) = a^(bc)
examples x^(-4) = 1/(x^4)
3^(-x) = 1/(3^x)
(2/x)^(-n) = (1/(2/x))^n = (x/2)^n
2^(-x^3) = 2^(-3x) = 1/(2^3x)
so for example
2^(-x) - (x)^(-n) + (-n)^(x^(-2)) touch each part only once, do what you can
1/(2^x) - 1/(x^n) + (-n)^(-2x) the third part needed two steps, so be it
1/(x^n) - 1/(x^n) + (1/((-n)^2x)